Colletotrichum lindemuthia- num in Phaseolus vulgaris seed. - Marcinkowska, Joanna Z.; Borucka, Krystyna (Plant Breeding and Seed Science, 2001)
There was found significant correlation between incidence of Colletotrichum lindemuthianum in Phaseolus vulgaris seeds and leaves, pods and stem infection by the pathogen under natural field condition of 1997-1999. There was find in this study positive relationship in the case of 7 genotypes evaluated at Radzików (Central Poland) and Jankowice (South-East of Poland). Cultivar Nida was infected only sporadically. All plots of cv. Prosna showed symptoms of antracnose. Infection degrees of cv. Mela were always the highest. Four tested breeding lines were shown to be susceptible on this pathogen.